Formation and Clearance of NETs in Health and Disease. - Knopf, Jasmin; Mahajan, Aparna; Munoz, Luis Enrique; Herrmann, Martin (Cells, 2022)
Neutrophils are the most abundant innate immune cells in humans and the first line of defense against invading pathogens [...].
EVALuna2:521519